Sensationalism of suffering: the 'Kerala Model' media discourse of poverty porn - Raj, Sony Jalarajan; Suresh, Adith K. (My University, 2026)
In a technologically advanced environment where it is hard to discern reality from fiction, narratives that paint a particular picture about incidents and regions, geopolitical contexts and cultures, and demographics and social structures reveal structural patterns regarding biased worldviews. The coverage of global conflicts and the reporting of protest movements reveal the way media narratives shape the reality of situations differently. For instance, Western media’s portrayal of issues in the Middle East has been criticized for their propagandist misrepresentations. The reporting of the Israeli-Palestinian conflict, the Black Lives Matter Movement in the United States, and the 2020-2021 Indian Farmers’ Protests are contemporary examples showing how media frames events within preconceived narratives by strategically highlighting or ignoring certain aspects of the story to create an agenda (Bhowmik and Fisher 2023; Carney and Kelekay 2022; Raj and Suresh 2024).
Keywords: popular media; sensationalism; Kerala Model; media discourse